Formation of superfluid liquid pocket in aerogel and its solidification by cooling: Сверхтекучесть в низкоразмерных системах и в условиях ограниченной геометрии - Matsuda, H.; Ochi, A.; Isozaki, R.; Nomura, R.; Okuda, Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Formation of superfluid liquid pockets of 4He surrounded by 4He crystals were observed in an aerogel of 96% porosity. The liquid pockets did not crystallize by application of pressure but crystallized via avalanche by cooling below a particular temperature. The crystallization by cooling was also observed when crystals occupied a smaller portion of the aerogel. Driving force for the crystallization by cooling and possible mass transport process are discussed.